Vanillin derivative inhibits quorum sensing and biofilm formation in Pseudomonas aeruginosa: a study in a Caenorhabditis elegans infection model. Issue 6 (19th March 2022) - Shastry, Rajesh P.; Ghate, Sudeep D.; Sukesh Kumar, B.; Srinath, B. S.; Kumar, Vasanth
Abstract: Vanillin and its derivative, (4-(( E )-(4-hydroxy-2-m ethylphenylimino) m ethyl)-2-methoxyp henol (MMP) were showed clear inhibition of violacein and pyocyanin at sub-MICs indicating a possible quorum quenching effect of both the compounds. MMP was able to inhibit the biofilm formation in Pseudomonas aeruginosa PAO1 at 125 μg/mL ( p <  0.05), while vanillin at 250 μg/mL ( p <  0.05) indicating that they act against quorum sensing regulated biofilm formation. The inhibition of biofilm was confirmed by visualization through fluorescence microscopy followed by docking analysis of molecules against quorum sensing activator proteins. Caenorhabditis elegans survival assay revealed that vanillin and MMP were able to increase survival of C. elegans from P. aeruginosa PAO1 infection. The study showed that the potent features of the MMP and vanillin in inhibiting the quorum sensing regulated virulence and biofilm, which was proved in C. elegans infection model as well as molecular docking studies. GRAPHICAL ABSTRACT: